2022
DOI: 10.1111/hae.14641
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity for people with haemophilia in the age of new treatments

Abstract: Haemophilia treatment has seen great advances in recent years with an accompanied reduced risk of physical activity (PA) related bleeds. Based on its known health benefits, people with haemophilia (PWH) are currently encouraged to regularly engage in PA. However, this may not always translate to increased levels of PA. In this narrative review we aim to provide a brief overview of what is currently understood regarding PA levels and influences for the three broad age groups of children and adolescents, adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Thus, we recommend haemophilia treaters to have extra focus on PA promotion for children and adolescents. This should include provision of individualised advice and support for PA, based on an up‐to‐date understanding of barriers and motivators for PA, including the unique challenges the person with haemophilia may face 41 . More information on the topic can be found elsewhere 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we recommend haemophilia treaters to have extra focus on PA promotion for children and adolescents. This should include provision of individualised advice and support for PA, based on an up‐to‐date understanding of barriers and motivators for PA, including the unique challenges the person with haemophilia may face 41 . More information on the topic can be found elsewhere 41 …”
Section: Discussionmentioning
confidence: 99%
“…This should include provision of individualised advice and support for PA, based on an up-to-date understanding of barriers and motivators for PA, including the unique challenges the person with haemophilia may face. 41 More information on the topic can be found elsewhere. 41 Interestingly, we found that MVPA was similar between groups although proportions of PWH participating in 'sport' at least once per week and undertaking at least one to three exercise sessions per week were significantly higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess weight in haemophilia has been reported to contribute to restrictions in range of movement and loss of joint mobility adding to the cumulative burden of the disease and impacting on function. 29 Time spent in MVPA was also a significant predictor; an increase of Promoting physical activity regardless of age and underlying disease is a WHO and haemophilia care priority as physical inactivity is a contributory risk for obesity and mortality, 27,28 with publications reporting sedentary behaviours comparable or reduced in comparison to their healthy peers. 16,17,25,26 Importantly, children with different severities of haemophilia performed differently on the 10 m-ISWT, indicating this is a discriminative clinical measure in this population (the difference between boys with inhibitors compared to mild/moderate group was significant).…”
Section: Discussionmentioning
confidence: 99%
“…Promoting physical activity regardless of age and underlying disease is a WHO and haemophilia care priority as physical inactivity is a contributory risk for obesity and mortality, 27,28 with publications reporting sedentary behaviours comparable or reduced in comparison to their healthy peers 16,17,25,26 …”
Section: Discussionmentioning
confidence: 99%